A Pilot Study on Electrical Impedance Tomography During CPAP Trial in Patients With Severe Acute Respiratory Syndrome Coronavirus 2 Pneumonia: The Bright Side of Non-invasive Ventilation - Rauseo, Michela; Mirabella, Lucia; Laforgia, Donato; Lamanna, Angela; Vetuschi, Paolo; Soriano, Elisa; Ugliola, Daniele; Casiello, Elena; Tullo, Livio; Cinnella, Gilda (Frontiers in Physiology, 2021)
Background: Different SARS-COv2 pneumonia phenotypes match with different lung compliance and oxygenation, thus requiring a personalized setting. The burden of so many patients and the lack of ICU bed, often force physicians to choose NIV as first approach, even if no consent has been reached to discriminate whether it is safe. Under such conditions, EIT, a non-invasive bedside tool, could be useful to assess patients’ response to NIV. Objective: The rationale behind this study is that de-recruitment is a more efficient measure of patients’ PEEP-dependency than recruitment. We hypothesized that patients who derecruit significantly when PEEP is reduced are the ones that do not need early intubation while small ΔEELV variations after a single step of PEEP de-escalation could be predictive of NIV failure. Material and Methods: Consecutive patients admitted to ICU with confirmed COV-SARS-2 pneumonia ventilated in NIV were enrolled. Exclusion criteria were former intubation or NIV lasting > 72 hours. A trial of CPAP 12 was applied in every patient for at least 15 min, followed by a second period of CPAP 6, either in supine and prone position. Besides standard monitoring, patient’s ventilation was assessed by EIT, and ΔEELI (%) was calculated as the difference in EELI between CPAP12 to CPAP6. Vt, Ve, RR,FiO2 and ABGs were recorded. Data were analyzed offline with the dedicated software. Patients outcomes in terms on intubation rate and ICU mortality were recorded. Results: We enrolled 10 male patients, mean age 67 years. Six patients (60%) were successfully treated by NIV until ICU discharge (Group S), four patients failed NIV and were intubated and switched to MV (Group F). All these patients died in ICU. During the supine CPAP decremental trial, all patients experienced an increase in RR and Ve. ΔEELI was < 40% in Group F and > 50% in Group S. In the prone trial, ΔEELI was >50% in all patients, while RR decreased in Group S and remained unchanged in Group F. Conclusions: ΔEELI < 40% after a single PEEP de-escalation step in supine position, seems to be a good predictor of poor recruitment and CPAP failure.